Impacts of the calcination temperature on the structural and radiation shielding properties of the NASICON compound synthesized from zircon minerals - Islam G. Alhindawy; Hany Gamal; Aljawhara.H. Almuqrin; M.I. Sayyed; K.A. Mahmoud (Nuclear Engineering and Technology, 2023)
The present work aims to fabricate Na1+xZr2SixP3-xO12 compound at various calcination temperatures based on the zircon mineral. The fabricated compound was calcinated at 250, 500, and 1000°C. The effect of calcination temperature on the structure, crystal phase, and radiation shielding properties was studied for the fabricated compound. The X-ray diffraction diffractometer demonstrates that, the monoclinic crystal phase appeared at a calcination temperature of 250°C and 500°C is totally transformed to a high-symmetry hexagonal crystal phase under a calcination temperature of 1000°C. The radiation shielding capacity was also qualified for the fabricated compounds using the Monte Carlo N-Particle transport code in the γ-photons energy interval between 15keV and 122keV. The impacts of calcination temperature on the γ-ray shielding behavior were clarified in the present study, where the linear attenuation coefficient was enhanced by 218% at energy of 122keV, when the calcination temperature increased from 250 to 1000°C, respectively.